2016
DOI: 10.1177/1753465816671697
|View full text |Cite
|
Sign up to set email alerts
|

Current best practice in the evaluation and management of malignant pleural effusions

Abstract: Malignant pleural effusions (MPEs) are an important cause of cancer-related mortality and morbidity. It is a heterogeneous group of conditions, which leads to debilitating symptoms and confers a poor prognosis. Recent well-designed randomized trials have provided a broader evidence base for an expanding range of treatment options. Together, with new prognostic scoring systems and a greater understanding of how different patient phenotypes respond to treatment, this allows greater personalization of management.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 71 publications
0
9
0
Order By: Relevance
“…Although the gold standard of MPE diagnosis is cytopathology, occasionally, several sampling times were required for identification of malignant cancer cells with microscopy. Various markers have been suggested as noninvasive tests to help discriminate between BPE and MPE and to provide prognostic information . The most heavily studied diagnostic biomarker in pleural effusion is carcinoembryonic antigen (CEA).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the gold standard of MPE diagnosis is cytopathology, occasionally, several sampling times were required for identification of malignant cancer cells with microscopy. Various markers have been suggested as noninvasive tests to help discriminate between BPE and MPE and to provide prognostic information . The most heavily studied diagnostic biomarker in pleural effusion is carcinoembryonic antigen (CEA).…”
Section: Discussionmentioning
confidence: 99%
“…Various markers have been suggested as noninvasive tests to help discriminate between BPE and MPE and to provide prognostic information. 16,17 The most heavily studied diagnostic biomarker in pleural effusion is carcinoembryonic antigen (CEA). A meta-analysis including 49 studies suggested that the pooled sensitivity and specificity of pleural effusion CEA for diagnosing MPE were 0.549 and 0.962.…”
Section: Discussionmentioning
confidence: 99%
“…Magnetic resonance (MR) offers better-quality images of soft tissue than CT scans. Therefore, MR has higher sensitivity to detect chest-wall and diaphragmatic involvement, although the lung images have a lower quality [ 23 ]. Although there are reports of sensitivity and specificity rates of 90% to differentiate malignant from benign PE, the optimal protocol has not yet been established.…”
Section: Diagnostic Testsmentioning
confidence: 99%
“…Exudative pleural effusion can be further classified as malignant or benign based on the detection of malignant cells in the pleural fluid. Pleural fluid of malignant pleural effusions (MPE) contains cancer cells, while benign pleural effusions (BPE) does not 6 . An accurate diagnosis of MPE is crucial, since MPE can be an indication of pleural metastases caused by lung cancer, breast cancer, ovarian cancer and lymphomas, with lung cancer being the leading cause 7 9 .…”
Section: Introductionmentioning
confidence: 99%